Self-reported eating traits: Underlying components of food responsivity and dietary restriction are positively related to BMI - Menna Price (Appetite, 2015)
Self-report measures of dietary restraint, disinhibited eating, hedonic response to food and loss of control over eating have been related to over eating, overweight and obesity. Impulsivity has emerged as a potential moderator in this relationship. However, the exact relationship between these measures and obesity is poorly defined. Self-report data was collected from a student and community based sample (N = 496) of males (N = 104) and females, with a wide age (18-73yrs; M = 27.41) and BMI (15.3-43.6; M = 24.2) range. Principle component analysis was used to explore the underlying structure of the sub-scales from a variety of eating behaviour questionnaires. Two emergent components relating to 'dietary restriction' and 'food reward responsivity' were supported in the analysis. Food reward responsivity component scores positively predicted BMI, but this relationship was moderated by impulsiveness. Dietary restriction component scores positively predicted BMI but were not moderated by impulsiveness. These findings suggest that frequently used eating behaviour measures can be reduced to two underlying components. Food reward responsivity positively predicts BMI, but only when impulsiveness is also high, supporting a dual-system approach where both bottom-up food reward drives and top-down impulse control are associated with overweight and obesity. Dietary restriction is an independent, positive predictor of BMI and is likely to be reflecting repeated unsuccessful attempts at weight control.